Evaluation Of Pharmacist'S Educational Intervention In Improving Treatment Outcomes Of Patients With Rheumatoid Arthritis - Naqvi, Atta Abbas (2019)
Pharmacist’s role in Pakistan’s healthcare system has traditionally been limited to dispensing of medications. Healthcare stakeholders and policy makers have repeatedly called for enhancing this role and involving pharmacists in direct patient care. Therefore, this study was aimed to evaluate pharmacist led educational intervention in improving treatment outcomes of patients with rheumatoid arthritis. A two arm-randomized single-blind controlled trial was designed. One arm was labeled as, ‘control’ group (CG), while other was, ‘intervention’ group (IG). The pharmacist provided an educational intervention in IG and usual care in CG. This study was conducted in rheumatology clinics of 7 hospitals in Karachi, Pakistan. A total of 714 patients were randomly enrolled, 354 in the IG and 360 in the CG.